A long-acting composite tracer material for oil, gas and water wells and preparation method thereof

In the oil and gas well production profile tracer testing technology, microcapsules are used to coat tracer and use specific monomers to prepare microcapsule emulsions, combined with epoxy resin and maleic anhydride, the problems of uncontrollable tracer release and scale are solved, and the controlled release and stable performance of long-acting composite tracer materials are achieved.

CN119735758AInactive Publication Date: 2025-04-01BEIJING CHENCHU PETROLEUM TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411919422.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing oil and gas well production profile tracer testing technology, uneven dispersion of tracer in polymer leads to uncontrollable release, and prone to scaling, resulting in hindered release, making it difficult to meet the needs of long-term composite tracer materials.

Method used

Microcapsules were used to coat tracers, and acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropanesulfonic acid were used as microcapsule wall materials to prepare a core-shell structure microcapsule emulsion by semi-continuous seed emulsion polymerization, combining epoxy resin and maleic anhydride to form a long-acting composite tracer material.

Benefits of technology

The controlled release rate of tracer is achieved, avoiding the initial release fluctuations and scaling problems, extending the release cycle, and improving the mechanical properties of the tracer material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207583120000071
    Figure BDA0005207583120000071
  • Figure BDA0005207583120000072
    Figure BDA0005207583120000072
  • Figure BDA0005207583120000081
    Figure BDA0005207583120000081
Patent Text Reader

Abstract

The invention discloses a long-acting composite tracer material for oil, gas and water wells and a preparation method thereof, and relates to the technical field of long-acting composite tracer materials. The invention prepares the tracer into microcapsules so that its release rate is more controllable, effectively avoiding large fluctuations in the early stage of release, and using acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid as microcapsule wall materials, itaconic anhydride and acrylic acid have excellent scale inhibition efficiency for calcium carbonate, and the introduction of sulfonic acid groups can also prevent the generation of gelation, so that the long-acting composite tracer material prepared by the present application can also effectively avoid scaling problems, thereby extending the release cycle, and the addition of microcapsule emulsion can also play a toughening and modification role on epoxy resin, effectively improving the mechanical properties of the original tracer material; wherein the itaconic anhydride used can play a partial curing role, so that the microcapsules can be firmly fixed in the epoxy resin skeleton as a curing core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of long-acting composite tracer materials, in particular to a long-acting composite tracer material for oil, gas and water wells and a preparation method thereof. Background Art

[0002] In the process of oil and gas well development, accurate understanding of the production profile of oil and gas wells is crucial for optimizing mining plans, improving recovery rates, and evaluating reservoir characteristics. Traditional methods for obtaining oil and gas well production profiles have many limitations and are difficult to meet the increasingly sophisticated needs of oil and gas mining. For example, conventional logging technology often cannot accurately distinguish the production contribution of each fracturing stage in complex reservoir environments, such as multi-layered and highly heterogeneous formations. Moreover, some indirect measurement methods may be affected by factors such as changes in formation fluid properties and interference from wellbore structures, resulting in large deviations in measurement results.

[0003] In this context, oil and gas well production profile tracer testing technology came into being. It performs specific operations on each section of fracturing fluid during the fracturing of oil and gas wells, that is, injecting tracer solution throughout the process, and then collecting samples at the wellhead and detecting the response of the tracer in the subsequent production stage. In this way, the dynamic changes of each fracturing section during the production process can be effectively tracked, and the production profile data of the oil and gas well can be accurately measured by in-depth analysis of the monitored tracer concentration output curves of each section. This not only helps to deepen the understanding of the internal structure of the reservoir, fluid distribution and other aspects, but also provides a reliable technical basis for evaluating the effects of process measures such as fracturing on improving the production performance of oil and gas wells, thereby playing an extremely critical role in the entire life cycle of oil and gas well development, and promoting oil and gas extraction technology to develop in a more efficient and accurate direction;

[0004] At present, most tracer materials use high molecular polymer as shell material to cover functional materials, and the release rate of functional materials is regulated by replacing the shell material or cross-linking agent. However, this control method has many disadvantages. For example, due to the uneven dispersion of the tracer in the polymer, its subsequent release is uncontrollable, and the coating method in this way will cause a large degree of release when it is just added, because the tracer that is easy to precipitate out of the outer layer during the initial addition process cannot be controlled to precipitate quickly, resulting in large initial fluctuations. Therefore, the present application adopts microcapsule coating and then mixing, so that its release rate can be controlled and there is no good release rate in the early, middle and late stages, and its release period is greatly extended;

[0005] As a long-lasting composite tracer material, it inevitably has a long-standing problem, that is, the surface is prone to scaling, which leads to the obstruction of later release. Therefore, this application uses acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid as microcapsule wall materials. Itaconic anhydride and acrylic acid have excellent scale inhibition efficiency on calcium carbonate, and the introduction of sulfonic acid groups can also prevent the occurrence of gelation. Therefore, the long-lasting composite tracer material prepared in this application can also effectively avoid scaling problems, thereby extending the release period. Summary of the invention

[0006] The purpose of the present invention is to provide a long-acting composite tracer material for oil, gas and water wells and a preparation method thereof, so as to solve the problems existing in the prior art.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A long-acting composite tracer material for oil, gas and water wells comprises microcapsule emulsion, epoxy resin 506 and maleic anhydride, wherein the mass ratio of the microcapsule emulsion, epoxy resin 506 and maleic anhydride is 1:1-1.2:0.2-0.25.

[0009] As an optimization, the microcapsule emulsion uses a tracer as the core and acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid as monomers to prepare a core-shell structured microcapsule emulsion by semi-continuous seed emulsion polymerization to synthesize a core-shell structured acrylate microcapsule emulsion.

[0010] As an optimization, the tracer is a fluorobenzoic acid tracer.

[0011] As an optimization, the tracer uses 2,6-difluorobenzoic acid.

[0012] As an optimization, microcapsule emulsion, epoxy resin 506 and maleic anhydride were weighed in a mass ratio of 1:1-1.2:0.2-0.25, and the microcapsule emulsion was added to the epoxy resin 506. The mixture was stirred for 3-3.5 hours at 120-125°C to form a uniform mixture. The mixture was then cooled to 90-95°C, maleic anhydride was added and stirred for 1-2 minutes, and then transferred to a steel mold. The mixture was cured at 80-85°C for 2-2.5 hours, and then cured at 145-150°C for 1-1.5 hours. The mixture was then naturally cooled to room temperature and demolded to obtain a long-lasting composite tracer material.

[0013] As an optimization, the steel mold is preheated to 80-85°C in advance.

[0014] As an optimization, the microcapsule emulsion comprises the following preparation steps: 2,6-difluorobenzoic acid, a compound emulsifier and a monomer mixture are weighed according to a mass ratio of 1: 0.15-0.18: 1.6-2.2, the monomer mixture and the compound emulsifier are equally divided into two parts, A and B, the monomer mixture B is prepared into a pre-emulsion for standby use, 2,6-difluorobenzoic acid and the compound emulsifier A are added to the monomer mixture A, ultrasonically dispersed for 30-35 minutes, heated to 60-65° C., potassium persulfate 0.01-0.015 times the mass of the monomer mixture A is dripped, and then the reaction is carried out at a constant temperature for 1-1.2 hours. After the reaction is completed, the temperature is cooled to 40° C., the colloid is filtered out, and the temperature is then raised to 60-65° C., the pre-emulsion and potassium persulfate 0.01-0.015 times the mass of the monomer mixture B are dripped at a uniform speed within 2-3 hours, the reaction is carried out at a constant temperature for 1-1.2 hours, and the temperature is cooled to room temperature after the reaction is completed to obtain a microcapsule emulsion.

[0015] As an optimization, the pre-emulsion is prepared by uniformly mixing the monomer mixture B and the compound emulsifier B, and then ultrasonicating for 30 to 35 minutes.

[0016] As an optimization, the compound emulsifier is prepared by mixing sodium lauryl sulfate and sodium polyoxyethylene fatty alcohol sulfate in a mass ratio of 3:0.8-1.

[0017] As an optimization, the monomer mixture is prepared by mixing acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1-1.2:1.4-1.6.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The release rate of the tracer is more controllable by preparing it into microcapsules, which effectively avoids large fluctuations in the early stage of release. Acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid are used as microcapsule wall materials. Itaconic anhydride and acrylic acid have excellent scale inhibition efficiency for calcium carbonate, and the introduction of sulfonic acid groups can also prevent the occurrence of gelation. Therefore, the long-lasting composite tracer material prepared in the present application can also effectively avoid scaling problems, thereby extending the release period. The addition of microcapsule emulsion can also play a toughening and modification role on the epoxy resin, effectively improving the mechanical properties of the original tracer material. The itaconic anhydride used can play a partial curing role, so that the microcapsules can be firmly fixed in the epoxy resin skeleton as a curing core. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] S1. Weigh 2,6-difluorobenzoic acid, compound emulsifier and monomer mixture according to the mass ratio of 1:0.15:1.6, divide the monomer mixture and compound emulsifier into two parts, A and B, prepare monomer mixture B into pre-emulsion for standby use, add 2,6-difluorobenzoic acid and compound emulsifier A to monomer mixture A, ultrasonically disperse for 30 minutes, heat to 60°C, add potassium persulfate 0.01 times the mass of monomer mixture A dropwise, and then react at a constant temperature for 1 hour. After the reaction is completed, cool to 40°C, filter to remove the colloid, then heat to 60°C, and heat for 2 hours. The pre-emulsion and potassium persulfate 0.01 times the mass of the monomer mixture B are uniformly added dropwise, and the reaction is carried out at a constant temperature for 1 hour. After the reaction is completed, the temperature is cooled to room temperature to obtain a microcapsule emulsion; the pre-emulsion is prepared by mixing the monomer mixture B and the compound emulsifier B evenly and ultrasonicating for 30 minutes; the compound emulsifier is prepared by mixing sodium dodecyl sulfate and sodium polyoxyethylene fatty alcohol ether sulfate in a mass ratio of 3:0.8; the monomer mixture is prepared by mixing acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1:1.4;

[0023] S2. Weigh microcapsule emulsion, epoxy resin 506 and maleic anhydride in a mass ratio of 1:1:0.2, add microcapsule emulsion to epoxy resin 506, stir for 3 hours at 120°C to form a uniform mixture, then cool to 90°C, add maleic anhydride and stir for 1 minute, transfer to a steel mold preheated to 80°C, cure at 80°C for 2 hours, then cure at 145°C for 1 hour, then naturally cool to room temperature and demold, to obtain a long-lasting composite tracer material.

[0024] Example 2

[0025] S1. Weigh 2,6-difluorobenzoic acid, compound emulsifier and monomer mixture according to the mass ratio of 1:0.165:1.9, divide the monomer mixture and compound emulsifier into two parts, A and B, prepare monomer mixture B into pre-emulsion for standby use, add 2,6-difluorobenzoic acid and compound emulsifier A to monomer mixture A, ultrasonically disperse for 32.5 minutes, heat to 62.5°C, add potassium persulfate 0.0125 times the mass of monomer mixture A dropwise, and then react at a constant temperature for 1.1 hours. After the reaction is completed, cool to 40°C, filter to remove the colloid, then heat to 62.5°C, and heat at 2 The pre-emulsion and potassium persulfate 0.0125 times the mass of the monomer mixture B were uniformly added dropwise within .5 hours, and the reaction was carried out at a constant temperature for 1.1 hours. After the reaction was completed, the temperature was lowered to room temperature to obtain a microcapsule emulsion; the pre-emulsion was prepared by mixing the monomer mixture B and the compound emulsifier B evenly and then ultrasonicating for 32.5 minutes; the compound emulsifier was prepared by mixing sodium dodecyl sulfate and sodium polyoxyethylene fatty alcohol ether sulfate in a mass ratio of 3:0.9; the monomer mixture was prepared by mixing acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1.1:1.5;

[0026] S2. Weigh microcapsule emulsion, epoxy resin 506 and maleic anhydride in a mass ratio of 1:1.1:0.225, add microcapsule emulsion to epoxy resin 506, stir for 3.25 hours at 122.5°C to form a uniform mixture, then cool to 92.5°C, add maleic anhydride and stir for 1.5 minutes, transfer to a steel mold preheated to 82.5°C, cure at 82.5°C for 2.25 hours, then cure at 147.5°C for 1.25 hours, then naturally cool to room temperature and demold, to obtain a long-lasting composite tracer material.

[0027] Example 3

[0028] S1. Weigh 2,6-difluorobenzoic acid, compound emulsifier and monomer mixture according to the mass ratio of 1:0.18:2.2, divide the monomer mixture and compound emulsifier into two parts, A and B, prepare monomer mixture B into pre-emulsion for standby use, add 2,6-difluorobenzoic acid and compound emulsifier A to monomer mixture A, ultrasonically disperse for 35 minutes, heat to 65°C, add potassium persulfate 0.015 times the mass of monomer mixture A dropwise, and then react at a constant temperature for 1.2 hours. After the reaction is completed, cool to 40°C, filter to remove the colloid, then heat to 65°C, and heat for 3 hours. The pre-emulsion and potassium persulfate 0.015 times the mass of the monomer mixture B were uniformly added dropwise, and the reaction was carried out at a constant temperature for 1.2 hours. After the reaction was completed, the temperature was cooled to room temperature to obtain a microcapsule emulsion; the pre-emulsion was prepared by mixing the monomer mixture B and the compound emulsifier B evenly and ultrasonicating for 35 minutes; the compound emulsifier was prepared by mixing sodium dodecyl sulfate and sodium polyoxyethylene fatty alcohol ether sulfate in a mass ratio of 3:1; the monomer mixture was prepared by mixing acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1.2:1.6;

[0029] S2. Weigh microcapsule emulsion, epoxy resin 506 and maleic anhydride in a mass ratio of 1:1.2:0.25, add microcapsule emulsion to epoxy resin 506, stir for 3.5 hours at 125°C to form a uniform mixture, then cool to 95°C, add maleic anhydride and stir for 2 minutes, transfer to a steel mold preheated to 85°C, cure at 85°C for 2.5 hours, then cure at 150°C for 1.5 hours, then naturally cool to room temperature and demold to obtain a long-lasting composite tracer material.

[0030] Example 4

[0031] The only difference from Example 2 is that the microcapsule emulsion in S2 is changed to 2,6-difluorobenzoic acid.

[0032] Example 5

[0033] The only difference from Example 2 is that the monomer mixture in S1 is prepared by mixing acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1.1:1.5, and is modified to be prepared by mixing acrylic acid and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1.5.

[0034] Test Example 1

[0035] Performance test at different temperatures and pH:

[0036] Test at different temperatures: Take 3 small pieces of sample, accurately weigh the initial mass and calculate the 2,6-difluorobenzoic acid tracer content; place the sample pieces in 200 mL of deionized water, respectively, and place them in the corresponding environment of 50°C, 70°C and 90°C; at a certain time interval, use LC-MS to measure the concentration of 2,6-fluorobenzoic acid solution. After each measurement, pour out the original solution, add 200 mL of distilled water and return to the corresponding environment, calculate the tracer release amount each time according to the measured concentration and solution volume and accumulate, and divide the cumulative release amount by the initial tracer content in the sample to obtain the cumulative release rate.

[0037] Performance test at different pH values: In the simulated environment, sulfuric acid and sodium hydroxide were used to prepare solutions with pH values ​​of 5.0 and 10.0, respectively, and three small sample blocks were taken, the initial mass was weighed, and the content of 2,6-difluorobenzoic acid tracer in the sample blocks was calculated. The three sample blocks were placed in 200 mL of deionized water and the previously prepared pH5.0 and pH10.0 solutions, respectively, and placed in a 70°C environment, and the concentration of 2,6-fluorobenzoic acid solution was measured regularly. After each measurement, the original solution was poured out, 200 mL of the corresponding solution was added again and placed back in the corresponding environment. The tracer release amount was calculated and accumulated according to the measured concentration and solution volume, and the cumulative release amount was divided by the initial tracer content in the sample to obtain the cumulative release rate.

[0038] Table 1- Experimental data of performance test at different temperatures

[0039]

[0040] Table 2 - Experimental data of different pH performance tests

[0041]

[0042] Impact strength test: Take the cured sample and process it into a 64mm×13mm×4mm specimen. Use a notch sample making machine to prepare a notch with a depth of about 2.5mm on the specimen. According to ASTMD256-97 standard, install the notched specimen on the cantilever beam impact test device. Start the test device to make the pendulum impact the specimen. Record the energy absorbed by the specimen during the impact process and other related data to calculate the impact strength.

[0043] Table 2 - Impact strength performance test data

[0044]

[0045] It can be seen from the release data at different temperatures that Examples 1 to 3 all performed well in terms of release rate control and impact strength. The release rate was controllable when just added, with little fluctuation. After 161 days, the lowest release rate was only 41.1%. Although the release rate was different at different temperatures, this was predictable. The release rate of Example 4 was the worst because it only relied on the epoxy resin skeleton to control the release, resulting in a large initial release. Although it can continue to work later, this experiment was tested in still water, so it will fail faster in actual work; the decline in Example 5 was also predictable. The lack of anhydride would cause its microcapsules to be loosely fixed in the epoxy resin, resulting in faster release.

[0046] From the release data under different pH conditions, it can be seen that the overall release rate is significantly faster in an alkaline environment, regardless of whether the microcapsules are coated or not. This is related to the tracer used. In an alkaline environment, it is easier to react with different ions in water to accelerate the release, and the microcapsule wall material used is also easier to decompose in an alkaline environment. Therefore, it is foreseeable that the release rate will be accelerated under alkaline conditions. From the final results, the release rate is accelerated but still within an acceptable range, and even in an alkaline environment, it only releases 47.4% at most. Therefore, even in an alkaline environment, it can still maintain a long-term stable release effect.

[0047] From the mechanical property test, it can be seen that the overall toughness of the resin modified with microcapsule emulsion has increased, and its impact resistance has been enhanced, which can make it better adapt to the working environment. Combined with the above release data, it can be seen that the release degree always maintains a relatively good increasing curve without large fluctuations, which also shows that it has not experienced rigid damage such as cracking.

[0048] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A long-lasting composite tracer material for oil, gas and water wells, characterized in that: The invention comprises microcapsule emulsion, epoxy resin 506 and maleic anhydride, wherein the mass ratio of the microcapsule emulsion, epoxy resin 506 and maleic anhydride is 1:1-1.2:0.2-0.

25.

2. The long-acting composite tracer material for oil, gas and water wells according to claim 1, characterized in that: The microcapsule emulsion uses a tracer as a core and acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid as monomers. The core-shell structured microcapsule emulsion is prepared by semi-continuous seed emulsion polymerization to synthesize the core-shell structured acrylate microcapsule emulsion.

3. The long-acting composite tracer material for oil, gas and water wells according to claim 2, characterized in that: The tracer is a fluorobenzoic acid tracer.

4. The long-acting composite tracer material for oil, gas and water wells according to claim 2, characterized in that: The tracer is 2,6-difluorobenzoic acid.

5. A method for preparing a long-acting composite tracer material for oil, gas and water wells, characterized in that: The method comprises the following steps: weighing microcapsule emulsion, epoxy resin 506 and maleic anhydride in a mass ratio of 1:1-1.2:0.2-0.25, adding the microcapsule emulsion into the epoxy resin 506, stirring for 3-3.5 hours at a temperature of 120-125°C to form a uniform mixture, cooling to 90-95°C, adding maleic anhydride and stirring for 1-2 minutes, transferring to a steel mold, curing for 2-2.5 hours at a temperature of 80-85°C, curing for 1-1.5 hours at a temperature of 145-150°C, and naturally cooling to room temperature for demoulding to obtain a long-acting composite tracer material.

6. The method for preparing a long-acting composite tracer material for oil, gas and water wells according to claim 4, characterized in that: The steel mold is preheated to 80-85°C in advance.

7. The method for preparing a long-acting composite tracer material for oil, gas and water wells according to claim 4, characterized in that: The microcapsule emulsion comprises the following preparation steps: weighing 2,6-difluorobenzoic acid, a compound emulsifier and a monomer mixture according to a mass ratio of 1:0.15-0.18:1.6-2.2, dividing the monomer mixture and the compound emulsifier equally into two parts, A and B, preparing the monomer mixture B into a pre-emulsion for standby use, adding 2,6-difluorobenzoic acid and the compound emulsifier A to the monomer mixture A, ultrasonically dispersing for 30-35 minutes, heating to 60-65° C., dropping potassium persulfate in an amount of 0.01-0.015 times the mass of the monomer mixture A, then reacting at a constant temperature for 1-1.2 hours, cooling to 40° C. after the reaction is completed, filtering to remove colloid, then heating to 60-65° C., uniformly dropping the pre-emulsion and potassium persulfate in an amount of 0.01-0.015 times the mass of the monomer mixture B within 2-3 hours, reacting at a constant temperature for 1-1.2 hours, and cooling to room temperature after the reaction is completed to obtain the microcapsule emulsion.

8. The method for preparing a long-acting composite tracer material for oil, gas and water wells according to claim 7, characterized in that: The pre-emulsion is prepared by uniformly mixing a monomer mixture B and a compound emulsifier B and then ultrasonicating for 30 to 35 minutes.

9. The method for preparing a long-acting composite tracer material for oil, gas and water wells according to claim 4, characterized in that: The compound emulsifier is prepared by mixing sodium lauryl sulfate and sodium fatty alcohol polyoxyethylene ether sulfate in a mass ratio of 3:0.8-1.

10. The method for preparing a long-acting composite tracer material for oil, gas and water wells according to claim 4, characterized in that: The monomer mixture is prepared by mixing acrylic acid, itaconic anhydride and 2-acrylamide-2-methylpropane sulfonic acid in a mass ratio of 3:1-1.2:1.4-1.6.

Citation Information

Patent Citations

  • Chemical combination tracer agent and use method thereof

    CN109469481A

  • Polymer agent, microcapsule antiscale agent for preventing sulfate scale of oil well and preparation method of microcapsule antiscale agent

    CN117777346A

  • Sustained release system for reservoir treatment and monitoring

    US20180298277A1